2017
DOI: 10.1063/1.5001609
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of boron-neutron capture therapy of malignant brain tumors

Abstract: Boron neutron capture therapy (BN T) is characterized by a selective effect directly on the cells of malignant tumors. The carried out research showed the perspective of the given kind of therapy concerning malignant tumors of the brain. However, the introduction of BNCT into clinical practice is hampered by the lack of a single protocol for the treatment of patients and the difficulty in using nuclear reactors to produce a neutron beam. This problem can be solved by using a compact accelerator as a source of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
0
3
0
5
Order By: Relevance
“…The tumor size reduction in animals irradiated without boron compounds was apparently due to the presence of a component of fast neutrons and gamma radiation in the beam which has a destructive effect on tumor cells. However, this component was benign to normal tissues, as we have previously shown that the flux of epithermal neutrons obtained at the accelerator does not affect the viability of laboratory animals at therapeutic doses and does not lead to any significant damage in vital organs (Kanygin et al 2017).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The tumor size reduction in animals irradiated without boron compounds was apparently due to the presence of a component of fast neutrons and gamma radiation in the beam which has a destructive effect on tumor cells. However, this component was benign to normal tissues, as we have previously shown that the flux of epithermal neutrons obtained at the accelerator does not affect the viability of laboratory animals at therapeutic doses and does not lead to any significant damage in vital organs (Kanygin et al 2017).…”
Section: Discussionmentioning
confidence: 86%
“…Irradiation was carried out 3 weeks after orthotopic xenotransplantation of U87 human glioblastoma cells to mice thighs when tumor volumes reached 90-110 mm 3 (Kanygin et al 2017). Tumor sizes were monitored using high-field magnetic resonance (MR) imaging (11.7 T, BioSpec 117/16 USR, Bruker, Billerica, MA, USA) by directly estimating the linear dimensions of the tumor using T1-and T2-weighted MR imaging techniques.…”
Section: Irradiation Experimentsmentioning
confidence: 99%
“…1А, Б). Наши данные согласуются с предыдущими исследованиями по облучению клеточных линий U251MG, CHO-K1, V79 на ускорителе с током 1,5-3,0 мA при энергии протонов 2 МэВ [9], а также по аналогичному облучению клеточной линии U87 пучком с энергией протонов 2 МэВ и током 2,6 мА [11]. А.…”
Section: результаты исследования и их обсуждениеunclassified
“…Более того, ускорители нейтронов можно поместить в клинику. Оптимально терапевтический пучок нейтронов обеспечивается реакциями 7 Li(p,n) 7 Be или 9 Be(p,n) 9 B из-за низкой энергии генерируемых нейтронов [8].…”
unclassified
See 1 more Smart Citation